Role of a co-metal in bimetallic Ni-Pt catalyst for hydrogenation of m-dinitrobenzene to m-phenylenediamine - Telkar, M. M.; Nadgeri, J. M.; Rode, C. V.; Chaudhari, R. (Applied Catalysis A-General, 2005)
Bimetallic Ni-Pt catalysts supported on carbon were found to give very high turn over frequency numbers and almost complete selectivity to m-phenylenediamine in m-dinitrobenzene hydrogenation as compared to the monometallic nickel catalysts. The XRD and XPS characterization revealed that most of the nickel remains as Ni2+ in a monometallic catalyst while, the addition of platinum leads to the stabilization of Ni-0 state, in case of bimetallic catalysts. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Bimetallic catalyst; Catalytic hydrogenation; m-dinitrobenzene; m-phenylenediamine; Selective hydrogenation; turn over number; XPS and XRD of nickel

Ring hydrogenation of naphthalene and 1-naphthol over supported metal catalysts in supercritical carbon dioxide solvent - Shirai, M.; Rode, C. V.; Mine, Eiichi; Sasaki, A.; Sato, O.; Hiyoshi, Norihito (Catalysis Today, 2006)
Catalytic ring hydrogenations of naphthalene and 1-naphthol were studied over several supported metal catalysts in supercritical carbon dioxide solvent at low temperature. Higher concentration of hydrogen in supercritical carbon dioxide and lower reaction temperature were responsible for higher catalyst activity and selectivities to the desired partial ring hydrogenated products as compared with those observed in organic solvent for the same catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 1-naphthol; Hydrogenation; Naphthalene; Supercritical carbon dioxide; supported metal catalyst

Reaction kinetics of liquid phase air oxidation of p-cresol to p-hydroxybenzaldehyde - Kshirsagar, V. S.; Nadgeri, J. M.; Tayade, P. R.; Rode, C. V. (Applied Catalysis A-General, 2008)
The kinetics of liquid phase oxidation of p-cresol to p-hydroxybenzaldehyde has been investigated using insoluble cobalt oxide (CO3O4) catalyst at oxygen partial pressures in the range 0.1-1.5 MPa, reaction temperatures 333-393 K, p-cresol concentrations 0.49-1.53 kmol/m(3) and catalyst loadings 0.38-3.03 kg/m(3). The effects of oxygen partial pressure, reaction temperature, p-cresol concentration and catalyst loading on the initial rate of reaction have been studied. The initial rate varied linearly with catalyst loading up to 1.5 kg/m(3) beyond which it was independent of the catalyst loading while first-order dependence was observed with variation in oxygen partial pressure. A rate expression has been proposed considering Langmuir-Hinshelwood (LH) type mechanism, based on the initial rate data. A batch reactor model was also developed based on the kinetics studied and the concentration time profile predicted by the model was in good agreement with the experimental data. The activation energy for the liquid phase oxidation of p-cresol was found to be 39.6 kJ/mol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Co3O4; kinetics; p-cresol oxidation; XPS; XRD

Recovery of ammonical salts from mother liquid of 2-methyl-5-nitroimidazole - Dongare, Mohan K.; Rode, C. V.; Chandorkar, J. G. (Asian Journal of Chemistry, 2008)
An attempt have been made to recover the ammonical salt (ammonium sulphate and ammonium nitrate) from the mother liquid of 2-methyl-5-nitroimidazole successfully.
Keywords: 2-methyl-5-nitroimidazole; ammonium nitrate; ammonium sulphate; Recovery

Role of promoters in copper chromite catalysts for hydrogenolysis of glycerol - Mane, R. B.; Ghalwadkar, Ajay A.; Hengne, Amol M.; Suryawanshi, Y. R.; Rode, C. V. (Catalysis Today, 2011)
Various copper chromite catalysts with and without promoters were prepared by simultaneous co-precipitation and digestion technique and the role of promoters (Al, Ba and Zn) was investigated for hydrogenolysis of glycerol to 1,2-propylene glycol (1,2-PG) in both batch and continuous operations. Among various promoters studied, copper chromite catalyst with Ba as a promoter showed the highest activity and selectivity of 85% to 1,2-PG. This catalyst was found to be active for more than 800 h in a continuous operation also. Ammonia TPD results showed that barium promoted copper chromite catalyst had the highest acidity which facilitates the dehydration of glycerol to acetol which is the first step in hydrogenolysis of glycerol to 1,2-PG. The effect of barium content and variation in the promoters combination was also studied. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propylene glycol; Acetol; Ammonia TPD; Glycerol hydrogenolysis; Surface acidity